Nordic genre film : small nation film cultures in the global marketplace - Gustafsson, Tommy, 1969-; Kääpä, Pietari, 1977- (Traditions in world cinema., 2015)
A comparative approach to contemporary popular Nordic genre film Nordic Genre Film offers a transnational approach to studying contemporary genre production in Nordic cinema. It discusses a range of internationally renowned examples, from Nordic noir such as the television show The Bridge and films like Insomnia (1997) to high concept 'video generation' productions such as Iron Sky (2012). Yet, genre, at least in this context, indicates both a complex strategy for domestic and international competition as well as an analytical means to identify the Nordic film cultures' relationships to international trends. Conceptualizing Nordic genre film as an industrial and cultural phenomenon, other contributions focus on road movies, the horror film, autobiographical films, the quirky comedy, musicals, historical epics and pornography. These are contextualized by discussion of their place in their respective national film and media histories as well as their influence on other Nordic countries and beyond. By highlighting similarities and differences between the countries, as well as the often diverse production modes of each country, as well as the connections that have historically existed, the book works at the intersections of film and cultural studies and combines industrial perspectives and in depth discussion of specific films, while also offering historical perspectives on each genre as it comes to production, distribution and reception of popular contemporary genre film.